Electromagnetic Properties Of Materials And Some Prediction Remarks - Yıldırım, Osman (Incdtp-Icpi, Ion Minulescu 93, 3Rd Sector, Bucharest, 031215, Romania, 2010)
Nondestructive techniques by using electromagnetic waves in many disciplines such as agriculture, engineering geology, material sciences and so on, are very important regarding predictions. As it is well-known, material properties can be determined by using electromagnetic waves. The scattering of electromagnetic waves due to physical and geometrical discontinuity is creating surface waves which are still dominant in prediction of material properties. A dielectric sheet on the ground plane will act as a guiding structure for surface waves. Matching the magnetic and electric field components across the air-dielectric boundary gives surface wave modes. Surface waves and related currents may be analyzed by using Wiener-Hopf technique. One of the components of the scattered field is the surface wave, propagating along the air-ground interface. Wiener-Hopf showed that a certain singular integral equation could be solved exactly using the theory of Complex Fourier transforms and functions of a complex variable. This method of solution is known as the Wiener-Hopf technique. In order to explain electromagnetic wave scattering, we have to find the solution of Maxwel equations by using boundary or mixed boundary conditions. Wiener-Hopf technique is very important tool in the solution of scattering problems having special geometrical structures. Wiener-Hopf geometries (half plane, cylinder, strip geometry, step discontinuity, double step discontinuity or strip with thickness) and related solution methods under Wiener-Hopf analysis have been studied.
Keywords: electromagnetics; Wiener-Hopf technique; scattering; diffraction; elektromanyetik; Wiener-Hopf tekniği; saçılma; kırınım